The aims of this experiment were to study the physical and chemical properties of meat of Brahman Cross, Angus and Murray Grey cattle. Forty cattle consist of Brahman Cross, Angus and Murray Grey were used in this study. All animals were kept in feedlot with ad libitum ration and water. Data were analyzed by using covariance analysis. Result shows that breeds were significantly influenced of physical and chemical properties of meat. The Murray Grey meat was tenderness (P<0,05) than Angus and Bra - Bram Brahmantiyo (Media Veteriner, 2000)
The aims of this experiment were to study the physical and chemical properties of meat of Brahman Cross, Angus and Murray Grey cattle. Forty cattle consist of Brahman Cross, Angus and Murray Grey were used in this study. All animals were kept in feedlot with ad libitum ration and water. Data were analyzed by using covariance analysis. Result shows that breeds were significantly influenced of physical and chemical properties of meat. The Murray Grey meat was tenderness (P<0,05) than Angus and Brahman Cross. The meat of Brahman Cross was less fat content (P<0,05) than Angus dan Murray Grey.